Training wheelchair tennis players: A strength and conditioning approach - Roetert, E. P.; Allen, J.; Davies, K.; Harnett, J.; Ochi, S. (Strength and Conditioning Journal, 2023)
The sport of wheelchair tennis has experienced significant growth in the United States, both at the grassroots and professional arenas. Much of this growth is due to the United States Tennis Association (USTA) taking control over the Paralympic side of the sport in 1998, followed by full integration of wheelchair tennis into the various business units of the organization in 2021. This led to the availability of greater resources benefiting USTA Player Development and high performance athletes. One of the most apparent benefits is using strength and conditioning USTA as the national professionals to improve athletic performance and decrease injury prevalence. Wheelchair tennis coaches and strength and conditioning professionals have collaborated to design innovative adaptations and accommodations. Therefore, the aim of this paper is to highlight the significant business and organizational progress made by the USTA as the National Governing Body for the sport of tennis, as well as to address practical strategies to develop and implement wheelchair players' specific strength and conditioning needs.